Mycobacterium intermedium granulomatous pneumonia in a green oropendola (Psarocolius viridis) - Kik, M. J. L.; Houwers, D. J.; Dinkla, A. (Veterinary record, 2010)
Blood chemistry revealed a lowered albumin fraction and elevated Î±, Î² and [GAMMA] globulins and an albumin:globulin ratio of 0.31, indicating chronic disease. Tissue samples from the lung were collected for histology and fixed in 4 per cent phosphate-buffered formalin, embedded in paraffin, sectioned at 4 Î¼m and stained with haematoxylin and eosin and ZN.